(untitled) (FULAFIA IAC Book of Proceedings, 2024)
River Rutu and Doma dam in Doma LGA of Nasarawa state were analyzed for their physicochemical parameters and heavy metal concentrations. This was to ascertain the level of contamination and develop models for predictive purposes. Water samples were collected from each river in dry season twice (January & March) and same in the wet season (July & August). Physicochemical analyses were obtained using standard procedures while heavy metal concentrations were obtained using Atomic absorption spectrophotometer (AAS). Results showed that all physicochemical parameters analyzed were below the maximum tolerable limit by Nigerian Standard for Drinking Water Quality and the World Health Organization. Heavy metals analysed showed a general increase in concentration in the dry season with the exception of copper which showed a high concentration in the wet season in both study areas. Ni concentration in river Rutu was low and was not detected in Doma dam in the dry season. Data from physicochemical parameters and concentrations of respective heavy metals were inputted into the Minitab 18 statistical computer software for model development. The models developed for each heavy metal, Pb, Zn; Fe; Cu; Co; Cr and Mn were all multivariate in nature and noted to be statistically reliable at 95 % confidence limit. R2 values for all the models ranged from 65 to 98 %, implying that the developed models can be relied on in predicting the concentration of the respective heavy metals by measuring the physicochemical parameters and evaluating using each model.